Associations of chemical components of fine particulate matter with emergency department visits in Guangzhou, China. (1st February 2021) - Guo, Pi; Wu, Haisheng; Chen, Yuliang; Lv, Jiayun; Shi, Tongxing; Liu, Pengda; Wu, Yan; Zhou, Hongwei; Zhang, Hongfeng; Liu, Miao; Zheng, Murui; Feng, Wenru
Abstract: The magnitudes of toxicities and effects of the ambient concentration of total mass (weight) of particulate matter with aerodynamic diameter less than 2.5 μm (PM2.5 ) on adverse health outcomes manifest regional- and temporal-specific heterogeneity due to the variability of embedded chemical components. To explore acute hazards of 39 chemical components of PM2.5 on cause-specific emergency department visits (EDVs) in the Guangzhou, China, we firstly applied geographical detector method to quantify the individual and interactive effects of PM2.5 chemical components on the variability of EDVs. Then, a causal inference framework based on the Bayesian Additive Regression Trees (BART) was developed to estimate the causal impacts that would have had on cause-specific EDVs, under an assumptive intervention via setting median concentration of as the predefined threshold for each PM2.5 component. We found that the pairwise interactions of components play a more important role in explaining the variability of cause-specific EDVs than single factor separately. PM2.5 chemical components combined with gaseous pollutants as well as meteorological factors affect cause-specific diseases. We obtained robust causal estimates that exposures to high levels of vanadium and fluoranthene caused an increase in EDVs for neurological diseases (4.39%; 95% CI: 0.65%, 8.23%) and circulatory diseases (4.72%; 95% CI: 0.12%, 9.63%), respectively. A comprehensive strategy to reduce the hazards of toxic chemical components of PM2.5 is urgently needed. Highlights: Acute hazards of PM2.5  components on emergency department visits (EDVs) were assessed. The relationships between components and EDVs were evaluated within a causal inference framework. The impact of pairwise interactions of components on human health was identified. High levels of vanadium and fluoranthene were linked to neurologic and circulatory EDVs, respectively.